Al-Hajar Al-Aswad -The Honorable Black Stone Phenomenon - Madalieva Khonzoda (Periodica Journal, 2023)
This article discusses the phenomenon of sanctity, sacred concepts in the Islamic religion, the history of the phenomenon of the venerable black stone and its peculiarities. The teachings of Islam about the black stone are also mentioned
Keywords: Sanctity; al-hajar al-aswad; Ibrahim